Water-Energy-Food Nexus Sustainability in the Upper Blue Nile (UBN) Basin - Allam, Mariam M.; Eltahir, Elfatih A. B. (Frontiers in Environmental Science, 2019)
The Nile basin ecosystem is under stress due to rapid population growth, inefficient utilization of resources, climate change, and persistent conflicts among riparian countries. The Blue Nile is a major tributary of the Nile River and contributes about 60% of the total annual flow. This paper presents a framework for optimal allocation of land and water resources in the upper Blue Nile (UBN) basin. This framework consists of two optimization models that aim to: (a) allocate land and water resources optimally to rain-fed and irrigated agriculture, and (b) allocate water to agriculture and hydropower production while maximizing the total net benefits. The optimal agricultural expansion is expected to reduce the UBN flow by about 7.6 cubic kilometers, impacting the downstream countries Egypt and Sudan. Optimal operation rules for the Grand Ethiopian Renaissance dam (GERD) are identified to maximize annual hydropower generation from the dam while achieving a relatively uniform monthly production rate. Trade-offs between agricultural expansion and hydropower generation are analyzed in an attempt to define scenarios for cooperation that would achieve win-win outcomes for the three riparian countries sharing the basin waters